In situ observations lead to the discovery of the large ctenophore Kiyohimea usagi (Lobata: Eurhamphaeidae) in the eastern tropical Atlantic - Hoving, Henk-Jan; Neitzel, Philipp; Robison, Bruce (Zootaxa, 2018)
We report on the first records of Kiyohimea usagi Matsumoto & Robison 1992 (Ctenophora; Eurhamphaeidae) in the Atlantic Ocean. This large, fragile ctenophore cannot be captured by nets, and can only be studied in its natural habitat, the pelagic ocean. In the eastern Atlantic, in the Cape Verde region, in situ observations were obtained using the manned submersible JAGO and a towed pelagic observation system. Between 2015 and 2018 we documented 10 individuals which were encountered between 47–590 m depth. A description of the gastrovascular canal system is provided and potential feeding behavior is discussed. Our study confirms how in situ observations in the poorly explored pelagic realm will lead to the discovery of relatively large and previously undocumented fauna.